Current Social Domination Theory: Is It Still Relevant? - Sherly Mega Paranti; Joevarian Hudiyana (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
Social dominance theory (SDT) often used to explain intergroups conflict and discrimination phenomenon. SDT argues that society lives in a social system where hierarchy of social groups exist. In such conditions, violence, and pressure on one group is a manifestation of the dominant group maintaining its status over the subordinate group. At the beginning of its emergence, SDT received quite a lot of criticism for its theoretical premises. However, in recent years there has been no literature that attempted to re-examine or criticize SDT in current condition. Meanwhile, SDT researchers have developed many studies to address theoretical weaknesses, especially in the last 10 years. This study aims to review and provide critics of SDT referring to the current development and condition of SDT. The research method used in this study is a literature review on the development of SDT. The results showed that to date SDT still has several unsolved weaknesses despite the massive development of its research, including the inconsistency of claims to the universality of social hierarchy, inconsistency on SDO constructs, lack of empirical evidence on social stratification groupings, and weaknesses in the SDT research methodology. However, SDT still has strength and potential that makes it survive and relevant in social scientific studies, especially on how it looks at intergroup conflict in terms of social hierarchy, social dominance, and power. Teori dominasi sosial atau social dominance theory merupakan salah satu teori dalam psikologi sosial yang cukup sering digunakan untuk menjelaskan perilaku antarkelompok, khususnya terkait konflik dan diskriminasi antarkelompok. Teori ini menjelaskan bahwa masyarakat hidup dalam sistem sosial dimana terdapat hierarki atas kelompok-kelompok sosial. Dalam kondisi seperti itu, kekerasan dan tekanan pada suatu kelompok adalah bentuk kelompok dominan mempertahankan statusnya atas kelompok subordinat. Selama tiga dekade eksistensinya, teori dominasi sosial cukup banyak mendapatkan kritik atas premis-premis teorinya. Namun, teori ini tetap eksis bahkan dalam 10 tahun terakhir penerapan teori ini meluas hingga ranah politik dan komunikasi. Meskipun teori dominasi sosial cukup berkembang, nyatanya masih terdapat beberapa kritik yang belum terjawab hingga saat ini yang menjadi kelemahan teori. Review ini akan menyoroti kelemahan-kelemahan teori yang belum terjawab, antara lain ketidakkonsistenan teori atas klaim universalitas hierarki sosial dan konstruk SDO, kurangnya bukti empiris atas pengelompokan stratifikasi sosial, serta kelemahan metodologi penelitian SDT. Review juga akan membahas mengapa teori ini tetap bertahan di tengah-tengah kelemahan yang ada, terutama karena keunikan teori yang melihat konflik antarkelompok dari sisi hierarki sosial, dominasi sosial, dan power.